Study of Interaction Interface of Vehicles for Automatic Driving - Meng, Zhixin (Transactions on Computer Science and Intelligent Systems Research, 2024)
With the rapid development of the vehicle and information industries, the traditional vehicle has been transformed from a simple travel tool to an intelligent vehicle with comprehensive functions, intelligence, and rich information. As a standard function of intelligent vehicles, automated driving will greatly reduce or even replace humans for vehicle control, and the human-machine interaction system pays more attention to displaying the driving status and prompting the driver in an intuitive way, to make the driver fully trust the vehicle and obtain safe driving experience. In this paper, I study the development and current application of the interaction interface of vehicles. The main study objective is HUD (Head-Up Display). By introducing different technologies of HUDs, the study describes the examples of interaction interface of HUDs, analyzes the pros and cons of the different applications, and thus presents the direct impression and typical futuristic experience of interaction interface of vehicles. The paper also discusses the human’s natural behavior while driving and related future technology advancement is developing, and the driving environment which is the most important topic for the whole industry. The paper analyzes the interaction requirements of automated driving vehicles and summarizes the development trend of the human-machine interaction system for automated driving, which results in better understanding of interaction interface of vehicles.